EMPLOYEES’ JOB TRAINING AND COMPENSATION AS PREDICTORS OF CORPORATE PERFORMANCE (NAU Journal of Technology and Vocational Education, 2025)
The focus of this study was to evaluate the predictive powers of training, compensations on corporate performance (CP) using Nestlé Nigeria, Plc. Three research questions and a hypothesis were answered and tested. A descriptive research design of survey was used. The population comprised 1084 staff of Nestle Plc. in Ogun State. Seven hundred and fifty (750) staff were then selected as the sample using a purposive sampling technique. Three research instruments were used for data collection: Employees’ Job Training Questionnaire (r = .77), Employees’ Compensation Questionnaire (r = .81), and Corporate Performance Questionnaire (r = .76). Pearson Product Moment Correlation (PPMC) and Multiple Regression Analysis (MRA) were used to answer the three research questions and test the hypothesis at .05 level of significance. Results revealed that there were significant relationships between: on-the-job training and CP (r = 239, ƿ
Keywords: Employees’ job training; compensation; corporate; performance